A Secondary School Teacher’s description of the process of determining report card grades - Simon, Marielle; Tierney, Robin; Forgette-Giroux, Renée; Charland, Julie; Noonan, Brian; Duncan, Randy (McGill Journal of Education / Revue des sciences de l'éducation de McGill, 2010)
This paper presents a grade 10 mathematics teacher’s in-depth description of the process she uses to determine the final grade for the report card within a standards-based context. Her case was part of a three-year comparative study of grading practices of teachers from two Canadian provinces that differ in their level of standardization of education. Survey, interview, and document data provided by the teacher revealed clear tensions between current grading policy and principles particularly within mathematics.